Is Buying Back of Shares a Dangerous Financial Strategy? (Global Journal of Management and Business Research, 2015)
The motives for the share repurchase is the increase in the value per share, and enhance the priceearnings (P/E) multiples, replenishment of the pool of share available for employee incentive options, prevention of hostile takeovers, and an effective way to return surplus cash to shareholders. Share repurchase programs can convince the capital structure of the company in a more direct way. Buy back stock reduces the market capitalization of a particular company, which makes the company able to strengthen capital gearing ratio as per its preference. The study found that if a company uses buying back of shares as a financial strategy, it will lead to increase in its capital gearing when financing is made for stock repurchase in the form of debt.
Keywords: price-earnings (P/E) multiples; replenishment of the pool of share; financial strategy; it will lead to increase in its capital gearing